THE INFLUENCE OF THE TURKISH LANGUAGE ON THE GERMAN LANGUAGE - Merganova Nigora Mamadodilovna; Ismoilova Sarvinozxon Gʻulomjon qizi (Bright Mind Publishing, 2025)
The interaction between the Turkish and German languages has evolved primarily through historical, cultural, and social connections. This scholarly paper explores how Turkish has influenced German, focusing on changes in vocabulary, grammar, pronunciation, and syntax. The central aim of the study is to analyze the mutual influence between Turkish and German, identifying both similarities and differences in their development. Particular attention is given to Turkish loanwords, idiomatic expressions, and cultural elements that have entered German. Furthermore, the research incorporates perspectives from linguistics, lexicography, historical linguistics, and language teaching methodologies.
Keywords: Turkish language, German language, lexical influence, grammar, culture, linguistics, phraseology, historical linguistics, vocabulary.